Table of obstacle course scoring results for Military academy female cadets - Ranđelović, Mile P.; Milanović, Bojan Č. (Vojnotehnički glasnik / Military Technical Courier, 2017)
This paper presents the creation of a table for obstacle course scoring results, for female cadets. The table is created based on the results obtained by female cadets during four years of studying at the Military Academy in Belgrade. After creating and applying the scoring table,its influence on female cadets scoring results is investigated. The investigation has shown that the implementation of the scoring table has improved the results of female cadets in the obstacle course test for more than 45 seconds but less than 56 seconds in average.
Keywords: repetition frequency; cumulative distribution; z-test; female cadets; obstacle course scoring table